Production of Smokeless Biofuel Briquettes from Palm Kernel Shell Assisted with Slow Pyrolysis Treatment - Mohamad Azman, Nurul Alia; Che Pa, Nasrul Fikry (Progress in Engineering Application and Technology, 2021)
In the lack of systematic delivery of modern cooking fuels in developed countries, strategies have been adopted to use biomass residue that abounds in most of these countries. This is meant to substitute wood charcoal and thus limit forest harvesting for fuel purposes. For this cause, palm oil residue briquettes have been marketed as a safer substitute for wood charcoal for heating, cooking, and other industrial applications in both urban and rural populations. The main objectives of this study are to determine the feasibility of palm kernel shells by comparing combustion properties of PKS sample briquettes with commercialized wood charcoal and to determine the most suitable binding agent mixture ratio in biofuel briquettes. A laboratory experiment was conducted to determine the Physico-chemical characteristics of the briquettes. Slow pyrolysis treatment was conducted in a furnace at 200℃, 400℃, and 600℃ respectively. In addition to mixing palm kernel shell bio-char (PKSB) with two different binders namely starch and NaOH. Results of the physical characterization of the briquettes were as follows, moisture content (16.64% dry basis), ash content (45.19%), fixed carbon (43.07%), volatile matter (9.19%), and calorific value (14.85/kg). In this study, it is found that the PKS sample treated with a pyrolyzed temperature of 600℃ together mixed with 5% starch composition in biofuel briquette is the most suitable alternative for wood charcoal.